Interplay between Nrf2 and αB-crystallin in the lens and heart of zebrafish under proteostatic stress - Park, Jinhee; MacGavin, Samantha; Niederbrach, Laurie; Mchaourab, Hassane S. (Frontiers in Molecular Biosciences, 2023)
A coordinated oxidative stress response, partly triggered by the transcription factor Nrf2, protects cells from the continual production of reactive oxygen species. Left unbuffered, reactive oxygen species can lead to protein aggregation which has been implicated in a spectrum of diseases including cataract of the ocular lens and myopathy of the heart. While proteostasis is maintained by diverse families of heat shock proteins, the interplay between the oxidative and proteostatic stress responses in the lens and the heart have not been investigated. Capitalizing on multiple zebrafish lines that have compromised function of Nrf2 and/or the two zebrafish small heat-shock proteins alphaBa- and alphaBb-crystallin, we uncovered a transcriptional relationship that leads to a substantial increase in alphaBb-crystallin transcripts in the heart in response to compromised function of Nrf2. In the lens, the concomitant loss of function of Nrf2 and alphaBa-crystallin leads to upregulation of the cholesterol biosynthesis pathway thus mitigating the phenotypic consequences of the alphaBa-crystallin knockout. In contrast, abrogation of Nrf2 function accentuates the penetrance of a heart edema phenotype characteristic of embryos of alphaB-crystallin knockout lines. Multiple molecular pathways, such as genes involved in extracellular interactions and implicated in cardiomyopathy, are revealed from transcriptome profiling thus identifying novel targets for further investigation. Together our transcriptome/phenotypic analysis establishes an intersection between the oxidative stress and chaperone responses in the lens and the heart.